Frequency of Specific Cardiovascular Disease Risk Factors among Cameroonian Patients on Dialysis: The Cases of Anaemia, Inflammation, Phosphate, and Calcium. (22nd May 2016) - Pancha Mbouemboue, Olivier; Danbe, Olivier Djile; Tangyi Tamanji, Marcel; Ngoufack, Jacques Olivier
Abstract : Specific cardiovascular risk factors are known to contribute to increasing cardiovascular mortality in patients with chronic renal disease. However, little is known about their distribution in our population. This study aimed at determining the prevalence of anaemia, inflammation, and phosphocalcium disorders in Cameroonian patients on dialysis. Thirty-five participants with stage V chronic kidney disease (defined by glomerular filtration rate, GFR < 15 mL/1.73 m 3 ) of age at least 20 years on haemodialysis were randomly recruited. A control group composed of persons without a history of renal or cardiovascular disease was also recruited. Haemoglobin concentration, serum phosphate concentration, serum calcium concentration, and CRP status as a marker of inflammation were determined for all participants. Anaemia, phosphocalcium metabolic disorders, and a positive CRP result among haemodialysed patients were estimated at 94.3%, 61.6%, and 77.1%, respectively. Anaemia was diagnosed in all female patients compared to 92% in males, while a positive CRP result was recorded in 90% of females and 72% of males. No significant differences were observed on the distribution of studied specific cardiovascular risk factors with duration of dialysis. Among the factors studied, anaemia was the most encountered.